Oxidation of TbFe2: Microstructure of oxide-film by both theory and experiment. (January 2018) - Manwani, Krishna; Chelvane, Arout J.; Panda, Emila
Graphical abstract: Highlights: Formalism was developed to predict ultra-thin oxide overgrowth on TbFe2 substrate. TbFe2 samples were also annealed and oxidized by varying a range of conditions. Tb2 O3 oxide was found to form at all conditions. Fe was found to segregate on to TbFe2 substrate at higher annealing temperatures. Fe2 O3 was also found to form along with Tb2 O3 at higher annealing temperatures. Abstract: TbFe2 owing to its highest magnetostriction finds significant application in defence. However, its quality degradation due to oxidation poses an enormous challenge for being scaled up in a device. To this end, a detailed study by means of both the theory and experiment is performed here to understand the oxide-film overgrowth due to dry, thermal oxidation of TbFe2 . Then these results are discussed and compared, which is found to be in agreement with each other. Understanding developed in this study would help in tuning the substrate constituents for higher temperature application, where oxidation of the substrate is a major concern.